Cryotherapy and Whole Body Cooling: A Critical Review of Physiological Impacts on Elite Athletes - Tokarczyk, Wojciech; Demel, Karol; Dziedzic, Monika; Potoczek, Adriana; Talaska, Justyna; Kantor, Antoni; Pietrzak, Krzysztof; Dyląg, Adrian; Król, Jakub; Raputa, Kacper (Quality in Sport, 2025)
Background: Cryotherapy and whole-body cooling are widely adopted in sports medicine to enhance recovery and performance in elite athletes. Modern techniques like whole-body cryotherapy (WBC) reduce inflammation and muscle soreness, yet their physiological mechanisms and long-term safety remain debated. Purpose: This review assesses physiological impacts of cryotherapy on key systems (cardiovascular, neuromuscular, immune) and evaluates benefits, risks, and protocol standardization needs. Methods: PubMed literature (2012-2023) was systematically analyzed using keywords "cryotherapy," "whole-body cooling," and "elite athletes." Relevant studies on recovery, performance, and safety were synthesized, acknowledging design variability and language bias. Results: Cryotherapy reduces muscle damage markers (e.g., creatine kinase) and inflammation, aiding acute recovery and strength retention. WBC outperforms passive recovery but shows inconsistent efficacy versus cold-water immersion. Risks include hypothermia and blunted hypertrophy. Small samples and non-standardized protocols limit generalizability. Conclusions: Cryotherapy benefits elite athletes contextually, particularly for acute recovery. Implementation requires strict safety protocols (exposure limits, monitoring) and individualized approaches. Future studies should prioritize standardized parameters, long-term safety, and mechanistic insights into mitochondrial/neural adaptations to optimize athlete outcomes.